OBSESİF KOMPULSİF HASTALARDA KAUDAT NÜKLEUS VE PUTAMENDE DİFÜZYON AĞIRLIKLI MRG BULGULARI - AĞLAMIŞ, SERPİL (Fırat Üniveristesi, 2012)
Bu çalışmanın amacı, obsesif kompulsif hastalarda kaudat nükleus ve putamende difüzyon ağırlıklı manyetik rezonans görüntüleme (DA-MRG) bulgularını ortaya koymak ve sonuçları kontrol grubu ile karşılaştırmaktır.Çalışmaya 20 obsesif kompulsif hasta ve 20 sağlıklı gönüllü olgu alındı. Bu olgularda difüzyon ağırlıklı manyetik rezonans görüntüleme ile b600 ve b1000 gradient değerlerinde difüzyon ağırlıklı eko-planar görüntüler (EPI) alınıp, her grubun b600 ve b1000 değerlerinde görünür difüzyon katsayısı (Apparent Diffusion Coefficient=ADC) haritaları üzerinden kaudat nükleus ve putamenden ölçüm yapıldı.Kontrol grubunda b600 için ortalama ADC değerleri kaudat nükleusda 851,7 ± 101 x 10-6, putamende 794 ± 32 x10-6 sn/mm²; obsesif kompulsif hastalarda b600 için ortalama ADC değerleri kaudat nükleusda 841 ± 80 x 10-6, putamende 781 ± 34 x10-6 sn/mm² bulunmuştur. b1000 için sırasıyla kontrol grubunda 773 ± 47 x10-6 ; 720 ± 34 x10-6 sn/mm²; obsesif kompulsif hastalarında 747 ± 94 x 10-6 ; 696 ± 62 x 10-6 sn/mm² bulunmuştur.Obsesif kompulsif hastalarda DA-MRG incelemesi kontrol grubu ile karşılaştırıldığında ortalama kaudat nukleus ve putamendeki ADC değerlerinde istatistiksel olarak anlamlı değişiklik saptanmamıştır. Ayrıca hem obsesif kompulsif hastalarda hem de kontrol grubunda b600 ve b1000'de sağ ve sol kaudat nükleus ve putamen ADC değerleri arasında da anlamlı farklılık izlenmedi.

The aim of this study is to reveal the finding of diffusion-weighted magnetic resonance imaging at caudate nucleus and putamen in patients with obsessive-compulsive disorder and to compare results with the control group.The study included 20 patients with obsessive-compulsive disorders and 20 healthy volunteers. In these cases, diffusion-weighted magnetic resonance imaging (DW-MRI) and diffusion weighted echo-planar images (DW-EPI) at b600 and b1000 gradient values were taken and the measurements were made through the maps of Apparent Diffusion Coefficient (ADC) of each group at b600 and b1000 values from caudate nucleus and putamen.Mean ADC values at b600 for the control group were found as 851,7 ± 101 x 10-6 mm²/sec in caudate nucleus and as 794 ± 32 x10-6 mm²/sec in putamen; these values at b600 for obsessive-compulsive patients were found as 841 ± 80 x 10-6 mm²/sec in caudate nucleus and 781 ± 34 x10-6 mm²/sec in putamen. For b1000, 773 ± 47 x10-6 , 720 ± 34 x10-6 mm²/sec were found in control group, respectively; and 747 ± 94 x 10-6 ; 696 ± 62 x 10-6 mm²/sec were found in obsessive-compulsive patiens, respectively.When DW-MRI examination in obsessive-compulsive patients was compared with control group, mean ADC values in caudate nucleus and putamen were not found statistically significant change. In addition, there were no significant differences about the right and left caudate nucleus and putamen ADC values at the b600 and b1000 in the both of obsessive- compulsive patients and control group.
Diffusion MRI findings in patients with obsessive- compulsive caudate nucleus and putamen
Keywords: Radyoloji ve Nükleer Tıp